The holistic work engagement: A study In indonesia oil palm industry - Saputra, Nopriadi; ., Sasmoko; Bramantoro Abdinagoro, Sri (International Journal of Engineering and Technology, 2018)
Industry 4.0 encourages organizations to implement holistic framework in human resource development. It is imperative to align concept of work engagement into holistic framework. This study aims to conduct confirmatory factor analysis on holistic work engagement concept and was conducted on 477 supervisors and managers from Indonesia oil palm industry. The data was analyzed by using Lisrel 9.30 and the result explains that the measurement model of holistic work engagement has adequate validity and reliability. The measurement model of the higher order construct has better goodness of fit than first order one. Â